Modelling and simulation of mixed quieuing server pharmacy system with adjustable parameters - Rashida Abd Rashid (Institute of Engineering Mathematics, 2015)
This study contains the analysis of queuing system for arrival and departure time for patients about the amount of time spent before medication can be received at pharmacy unit of Hospital Tuanku Fauziah. The data of patient arrival and departure times are real data. It is collected over a period of 20 consecutive working days in June 2014 on 7.30 am to 5.30 pm, Monday to Friday.